2020
DOI: 10.21203/rs.3.rs-28701/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Self-reported loss of smell and taste in SARS-CoV-2 patients: primary care data to guide future early detection strategies

Abstract: The early identification of new cases of SARS-CoV-2 infection in primary care is of outmost importance in the current pandemia. We conducted a preliminary study involving 816 primary care patients undergoing RT-PCR testing for a suspicion of COVID-19. We examined the association between smell or taste disorders and a positive SARS-CoV-2 test, and computed the performance of these symptoms in predicting a positive test. Smell or taste disorders were significantly associated with positive RT-PCR with an adjusted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…This meta‐analysis is the first, to our knowledge, to comprehensively investigate the prevalence of taste disorders in patients with COVID‐19. This meta‐analysis was conducted with a substantial number of studies 3,4,8–10,12,19,21,34–37,41–87 and hence included a considerable number of participants, resulting in more robust estimates. The majority of the included studies confirmed COVID‐19 cases with the RT‐PCR technique, which strengthens our findings.…”
Section: Discussionmentioning
confidence: 99%
“…This meta‐analysis is the first, to our knowledge, to comprehensively investigate the prevalence of taste disorders in patients with COVID‐19. This meta‐analysis was conducted with a substantial number of studies 3,4,8–10,12,19,21,34–37,41–87 and hence included a considerable number of participants, resulting in more robust estimates. The majority of the included studies confirmed COVID‐19 cases with the RT‐PCR technique, which strengthens our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Since many otherwise asymptomatic carriers of COVID-19 have reductions in smell and/or taste, and since such an impairment is one of the earliest symptoms, it has been suggested that olfactory/gustatory deficits could be used as a valuable screening tool and for a preliminary diagnosis ( Bénézit and others 2020 ; Hopkins and others 2020 ; Parma and others 2020 ; Sedaghat and others 2020 ; Tong and others 2020 ; Tudrej and others 2020 ; Yan and others 2020 ). Such a screening is relatively cheap, and very fast, and could be implemented together with a subsequent gene- or protein-based test for viral particles.…”
Section: Anosmia As a Diagnostic Toolmentioning
confidence: 99%
“…Real-time symptom collection through an app seems to be an attractive method to screen for potential COVID-19 and Menni et al’s approach confirms the crucial value of specific symptoms, such as loss of smell and taste in the diagnosis of this infection ( 3–5 ). Yet the score they propose should not be applied as such for primary care patients as it does not appear to perform well in this population.…”
mentioning
confidence: 90%
“…We compared the main features of the population involved in Menni et al’s study, and the performance of their score, with data from a cross-sectional study conducted between 24 March and 29 April 2020 in Lyon (France) involving nearly 1200 primary care patients undergoing RT-PCR testing for COVID-19 suspicion ( Table 1 ) ( 3 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation